Methodological Basis And Pedagogical Principles Of Individual Approach In The Field Of Management (Eurasian Journal of Research, Development and Innovation, 2025)
The importance of an individual approach in the fields of management and pedagogy is very great. This approach takes into account the personal needs, abilities and psychoemotional state of each person, helps them to develop sustainably. In order to increase the efficiency of work and maximize the potential of each person, it is necessary to apply an individual approach. In management, these principles and methods are widely used in the effective management of human resources, and in pedagogy, in the educational process.